FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS PADA SEKTOR AGRICULTURE DI BEI - Nila Pusvikasari; Afia Sunarni (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This research was conducted to predict the influence of the independent variables used on the occurrence of financial distress. The object in this study is agricultural sector companies listed on IDX during 2012-2020. The sample obtained by purposive sampling method consisted of 13 companies in the agricultural sector with a total data of 117. This study used a logistic regression analysis method. The results showed that: The variable sales growth affects the occurrence of financial distress in the company, a positive value of β indicates a positive effect, so that when there is an increase in sales growth of a company, it can increase financial risk for the company because the company can be easier to issue debt which is also accompanied by the risk of default and can end up in financial distress for the company. The profitability variable (ROA) has an effect on the occurrence of financial distress, a negative value of β indicates a negative effect, so that if there is an increase in the level of profitability (ROA) of the company, there will also be an increase in company cash which will reduce the probability of financial distress.